2020
DOI: 10.1002/ese3.667
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of the co‐gasification of wood and polyethylene in a two‐stage gasifier

Abstract: Co‐gasification of wood mixed with 20% (mass fraction) of polyethylene (PE) in a two‐stage NOTAR® fixed‐bed gasifier was studied in the present paper. The ratio of air flow injected in the pyrolyzer and air flow injected in the oxidation zone is called the air ratio (AR). The AR of 0.35, 0.43, and 0.49 were used for test runs. Mass and energy balances were established. The study showed the feasibility of co‐gasification of wood mixed with 20% of PE in the two‐stage gasifier. However, considerable quantity of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In a study by Singh et al, waste cross-linked polyethylene (XLPE) was gasified in a semibatch fixed bed reactor using 75 vol % CO 2 . In that study, 2 g of CO 2 was consumed per gram of XLPE between 700 and 900 °C, which was mainly attributed to the dry reforming of radical volatiles (Table ). This illustrates the endothermic nature of the CO 2 consuming reactions such as dry reforming; therefore, as seen here, the consumption of CO 2 could be attributed to the dry reforming of volatiles, with the highest injection of 40 vol % CO 2 at both ERs showing the greatest degrees of CO 2 consumption.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study by Singh et al, waste cross-linked polyethylene (XLPE) was gasified in a semibatch fixed bed reactor using 75 vol % CO 2 . In that study, 2 g of CO 2 was consumed per gram of XLPE between 700 and 900 °C, which was mainly attributed to the dry reforming of radical volatiles (Table ). This illustrates the endothermic nature of the CO 2 consuming reactions such as dry reforming; therefore, as seen here, the consumption of CO 2 could be attributed to the dry reforming of volatiles, with the highest injection of 40 vol % CO 2 at both ERs showing the greatest degrees of CO 2 consumption.…”
Section: Resultsmentioning
confidence: 99%
“…The required mass for the feedstocks was measured separately, and then the components were mixed by hand with a spatula until a uniform mixture was achieved. It has been found that adding biomass to plastic feedstocks greatly reduces or eliminates operational clogging by preventing the melt phase from agglomerating, ,,, resulting in a well-mixed feed.…”
Section: Methodsmentioning
confidence: 99%
“…Using a gasifying temperature of 850°C and steam to O 2 ratio of 1:1, the waste plastic gasification resulted in the evolution of 35% H 2 . Harouna et al 15 reported the co‐gasification of wood and polyethylene in a two‐stage gasifier. At a temperature range of 200°C to 1000°C, and an air ratio of 0.43, 17.64 Vol.% of hydrogen was evolved from the co‐gasification process.…”
Section: Introductionmentioning
confidence: 99%